Implementasi Reservasi Dan Manajemen Penginapan Berbasis Web Dengan Metode Rapid Application Development - Axl Bhernov; Pastima Simanjuntak (STMIK Bina Nusantara Jaya Lubuk Linggau, 2026)
Many small lodging facilities still perform reservation processes manually using instant messaging and handwritten records. Such traditional methods often lead to issues including double bookings, delayed confirmation, and inaccurate transaction documentation. These problems were also identified at HAPDESKO Homestay, which serves as the case study in this research. To address these issues, a web-based reservation and lodging management system was developed using the Rapid Application Development (RAD) method. RAD enables rapid system development through iterative stages consisting of requirement planning, design workshop, construction, and cutover. The resulting system provides features such as independent room booking, real-time availability checking, payment proof uploads, and an administrator dashboard for verification and data management. Implementation results show that the system improves service efficiency and reduces administrative errors. Blackbox Testing further confirms that all functionalities operate according to the required specifications.